An Integrative Intervention Group Counseling Program for Adolescents' Shyness: Combining Positive and Pathological Interventions (Dual-Factor Model) - Eryilmaz, Ali; Altinsoy, Fatma (TURKISH EDUCATION ASSOC, 2021)
This study analyzes the effectiveness of the Integrative Intervention Group Counseling Program on shyness. The study was conducted with adolescents of ages 14 to 16 in high school. It was conducted by using the embedded mixed method in which both qualitative and quantitative techniques are employed together, and the intervention program is composed of 11 sessions each of which lasted 90 minutes. The Shyness Scale was used to measure the effectiveness of the program, and the program was also evaluated qualitatively. The analysis of the data was carried out by performing the Repeated Measure of Variance Analysis and the Mann Whitney U Test. According to the findings, adolescents not only overcame shyness, but also achieved positive changes in self-perception and actively engaging in life. According to the results, the program developed for intervening with shyness in adolescents was found to be effective.
Keywords: Shyness; Integrative intervention program; Positively focused intervention; Pathology focused intervention; Dual-factor model; SOCIAL-SKILLS; MENTAL-HEALTH; DEPRESSIVE SYMPTOMS; RISK-FACTOR; PSYCHOLOGY; HAPPINESS; SUPPORT; Education & Educational Research